Adjunctive Effect of Systemic Antibiotics in Regenerative/Reconstructive Periodontal Surgery—A Systematic Review with Meta-Analysis - Luigi Nibali; Jacopo Buti; Luigi Barbato; Francesco Cairo; Filippo Graziani; Søren Jepsen (Antibiotics, 2021)
Background and Objective: Systemic antibiotics (AB) are often used in conjunction with regenerative/reconstructive periodontal surgery of intrabony defects and furcations; however, their potential benefits have not been systematically assessed. Materials and Methods: Data were retrieved from two recent systematic reviews (a total of 105 randomized clinical trials (RCTs) on clinical and radiographic outcomes in intrabony defects (ID) and molars with furcation involvement (FI) treated by surgical access with regenerative techniques. Pair-wise meta-analysis of RCTs with and without AB was performed. Meta-regressions from single-arm (subgroup) RCTs including study arms with or without adjunctive AB were also conducted. Results: No statistically significant benefits of systemic AB with regard to PPD, CAL and bone gain were detected in ID by pair-wise meta-analysis. Meta-regression revealed increased PPD reduction (−0.91 mm, 95% CI = −1.30; −0.51, p < 0.001), CAL gain (−0.92 mm, 95% CI = −1.32; −0.52, p < 0.001) and bone gain (−1.08 mm, 95% CI = −1.63; −0.53, p < 0.001) in ID but not in any of the outcomes in FI for arms treated with AB vs. study arms treated with no AB. No clear differences in adverse events were detected between AB and non-AB groups. Conclusion: There is only weak indirect evidence that AB may provide additional benefits in terms of clinical improvements in the regenerative/reconstructive periodontal surgery of intrabony defects and no evidence for a benefit in furcations. Until new data are gained and in the context of antibiotic stewardship, it may be questionable to justify the adjunctive use of systemic antibiotics.